Evaluation of a resilience training program for college student-athletes: A pilot study - Sullivan, L.; Carter, J. E.; Houle, J.; Ding, K.; Hautmann, A.; Yang, J. (Journal of American College Health, 2021)
To determine if a resilience training program improved knowledge of and intention to use adaptive coping strategies among college student-athletes; and explore college student-athletes` experiences and satisfaction with program components. Participants: Division I college student-athletes. Methods: Pretest-posttest design with surveys completed at baseline and immediately post-program. Results: A total of 79 participants were included (n = 43 [54.4%] females; n = 36 [45.6%] males; Mage = 20.94, [SD = 1.05]). Overall intention to use adaptive coping strategies significantly increased from baseline (M = 29.05, SD = 4.50) to post-program (M = 32.38, SD = 5.62) (p = 0.0004), as did intentions to use the coping strategies seeking social support (p = 0.0037) and self-controlling (p = 0.0007). We found no statistically significant differences in knowledge scores from baseline to post-program. Conclusions: Resilience training may increase college student-athletes` likelihood of using adaptive coping strategies to manage academic and sport-related stressors.